The Cambridge companion to the Scottish Enlightenment - Broadie, Alexander (Cambridge University, 2013)
In this volume a distinguished team of contributors examines the writings of David Hume, Adam Smith, Thomas Reid, Adam Ferguson, Colin Maclaurin and other Scottish thinkers, in fields including philosophy, natural theology, economics, anthropology, natural science and law.